2010
DOI: 10.1016/j.soilbio.2010.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the plant growth promotion abilities of six bacterial isolates using Zea mays as indicator plant

Abstract: Zea mays, one of the most important cereals worldwide, is a plant not only with food and energy value, but also with phytoremediation potential. The use of plant growth promoting (PGP) rhizobacteria may constitute a biological alternative to increase crop yield and plant resistance to degraded environments. In search for PGP rhizobacteria strains, 6 bacterial isolates were isolated from a metal contaminated site, screened in vitro for their PGP characteristics and their effects on the growth of Z. mays were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
141
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 290 publications
(147 citation statements)
references
References 47 publications
3
141
0
3
Order By: Relevance
“…In this study, several isolates (1AP2, EC 34, 3ZP2 and EC 10) with high ability to produce IAA promoted white clover root biomass which suggests a relation between both parameters. There results were corroborated by Marques et al (2010) who reported a positive correlation between IAA-producing rhizobacteria and Zea mays root biomass promotion and by Khalid et al (2004) who showed that bacterial strains which produced the highest amount of IAA also increased growth of wheat. Promotion of root growth is one of the major markers by which the beneficial effect of PGPR is measured (Glick et al 1995).…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…In this study, several isolates (1AP2, EC 34, 3ZP2 and EC 10) with high ability to produce IAA promoted white clover root biomass which suggests a relation between both parameters. There results were corroborated by Marques et al (2010) who reported a positive correlation between IAA-producing rhizobacteria and Zea mays root biomass promotion and by Khalid et al (2004) who showed that bacterial strains which produced the highest amount of IAA also increased growth of wheat. Promotion of root growth is one of the major markers by which the beneficial effect of PGPR is measured (Glick et al 1995).…”
Section: Resultsmentioning
confidence: 55%
“…Ammonia production is another common trait in tested rhizobacteria (Table 1). NH 3 production by bacterial isolates may enhance plant growth, which was also seen by Marques et al (2010) that demonstrated a positive correlation between bacterial ammonia production and root and shoot elongation of Zea mays plants. Only 2 strains (ECX16 and 3C5) belonging to Arthrobacter genus showed ability to solubilize phosphate.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…reproduced under field, semi-field or even greenhouse conditions as the interaction between the associative PGPR and plants could be unstable (Marques et al, 2010;Zhender et al, 1999 et al, 2000).…”
Section: In-vitro Results Of Pgpr Species May Not Be Alwaysmentioning
confidence: 99%
“…Pseudomonads also play a decisive role in plant growth promotion through reduction of ethylene production by synthesizing 1-aminocyclopropane-1-carboxylate (ACC) deaminase. The ACC deaminase enzyme modulates the level of ethylene by hydrolyzing ACC in ammonia and α-ketobutyrate (Marques et al, 2010). Pseudomonas fluorescens strain Psd solubilizes inorganic zinc and produces nitrate reductase along with certain antioxidant enzymes such as glutathione reductase and peroxidase which eventually supports the growth of wheat (Sirohi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%